EFEKTIVITAS OPCW-UN JOINT MISSION DALAM UPAYA PENGHENTIAN PENGGUNAAN SENJATA KIMIA DI SURIAH - Raka Noveri; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this study was to determine the effectiveness of the OPCW's performance with various forms of business, one of which was through the OPCW-UN Joint Mission which received a mandate as a team responsible for destroying chemical weapons in Syria effectively and efficiently. This study uses an analytical framework of the effectiveness of international organizations based on a pluralism perspective. This study uses a qualitative descriptive method with the types and sources of data used are secondary data obtained from the official website of the OPCW, the United Nations, the OPCW-UN Joint Mission, international journals and other sources. The data collection technique in this study used the literature study method. Data analysis techniques through the stages of data reduction, presentation, and verification. This study focuses on the effectiveness of the OPCW-UN Joint Mission in eliminating the availability of chemical weapons by the Syrian Government through investigation, intervention and facilitation efforts. Based on the theory of international organization effectiveness by Frank Biermann and Steffen Bauer with the benchmark factors of Formal Competencies, Degree of Regime Embeddedness, Organizational Structure, Problem of Fit and Availability of Resources. The OPCW is considered quite effective in carrying out its duties as a chemical disarmament organization through a joint UN mission. All stages of disarmament have been carried out according to the OPCW-UN Joint Mission mission and in accordance with the mandate of the UN Security Council which is accompanied by a monthly progress report on the mission and always shows good progress reports so that the mission can be completed according to the existing timeline so that the OPCW was awarded the Nobel Awards. in 2013 for its success in the elimination of chemical weapons.Keywords: Effectiveness, chemical disarmament, OPCW-UN Joint Mission, Syria